Blended Learning to Fly - Dominic Pates; Ivan Sikora (University of West London, 2021)
Profound change hit Higher Education globally in Spring 2020, leaving campuses around the world closed to face-to-face teaching. Once universities reopen premises more fully, we may see a mix of more socially-distanced campuses and a wider use of online and blended learning. Could our experiences in blended synchronous learning indicate ways forward for teaching practices?